2006
DOI: 10.1021/jo060622o
|View full text |Cite
|
Sign up to set email alerts
|

Anthralin:  Primary Products of Its Redox Reactions

Abstract: One-electron reduction significantly enhances the ability of anthralin, 1, to act as a hydrogen atom donor. On annealing of an MTHF glass in which the radical anion of anthralin, 1 •-, is generated radiolytically, this species decays mainly by loss of H • to give the anthralyl anion, 2 -. On the other hand, radicals formed on radiolysis of matrices that are suitable for the generation of radical anions or cations are capable to abstract H• from anthralin to give the anthralyl radical, 2 • . Both 2 -and 2 • are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
(68 reference statements)
0
20
0
Order By: Relevance
“…If, however, a more easily oxidizable ''hole scavenger'' such as 1,4-diazabicyclooctane (DABCO) is added, radical anions of added substrates can be formed, provided that the anions of these substrates are bound in Ar. 10,25 Here we have exploited this technique to differentiate the spectra of radical cations and anions of PBQ. The optical spectrum obtained upon X-irradiation of 10 K Ar matrices containing ca.…”
Section: Resultsmentioning
confidence: 99%
“…If, however, a more easily oxidizable ''hole scavenger'' such as 1,4-diazabicyclooctane (DABCO) is added, radical anions of added substrates can be formed, provided that the anions of these substrates are bound in Ar. 10,25 Here we have exploited this technique to differentiate the spectra of radical cations and anions of PBQ. The optical spectrum obtained upon X-irradiation of 10 K Ar matrices containing ca.…”
Section: Resultsmentioning
confidence: 99%
“…Indole and its derivatives were obtained from Sigma/ Aldrich and purified by sublimation before use. The ionic liquid, 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM þ PF 6 À ), 4 was prepared according to literature procedures.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…Recently, we found that the glass quality does not change upon mixing BMIM þ PF 6 À with CH 2 Cl 2 , which has the advantage that it improves the solubility of many precursors and leads to a higher yield of radical cations on radiolysis due to its ability to scavenge electrons by dissociative attachment. 4 Quantum Chemical Calculations. The geometries of all species were optimized first by the well-established B3LYP/ 6-31G* method by which stationary points were also characterized by frequency calculations.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…1. A is a reactive compound characterized by complicated red-ox properties (Czerwinska et al, 2006;Psenichnyuk & Komolov, 2014) and it exhibits anomalous fluorescence with a Stokes shift of 10500 cm -1 , indicating large rearrangement in the excited state (Møller et al, 1998). The precise mode of biochemical action is not fully understood, but the application of UV radiation is known to increase the activity of the drug (Lapolla et al, 2011).…”
Section: Introductionmentioning
confidence: 99%